Evaluation of Different Standard Amino Acids to Enhance the Biomass, Lipid, Fatty Acid, and γ-Linolenic Acid Production in Rhizomucor pusillus and Mucor circinelloides - Mohamed, Hassan; Awad, Mohamed F.; Shah, Aabid Manzoor; Nazir, Yusuf; Naz, Tahira; Hassane, Abdallah; Nosheen, Shaista; Song, Yuanda (Frontiers in Nutrition, 2022)
Although it is well known that low nitrogen stimulates lipid accumulation in oleaginous microbes, few studies have been conducted in fungal species, especially on the impact of various nitrogen sources strategies. In this study, eighteen standard amino acids were tested as single nitrogen source on the growth, total fatty acids production, and yield of γ-linolenic acid (GLA) in Rhizomucor pusillus AUMC11616.A and Mucor circinelloides AUMC 6696.A isolated from unusual habitats. Among tested amino acids, arginine, asparagine besides, glycine and valine gave the maximum fungal biomass reached up to 14.6±0.2, 13.68±0.1, 10.73±0.8 and 9.44±0.6 g/L, in AUMC11616.A and AUMC 6696.A, respectively, compared to ammonium tartrate. And high levels of total fatty acids production were achieved when glycine and glutamic acid were employed at 26.2±0.8 and 23.1±1.3 % of cell biomass, respectively, and thus resulted in a high GLA yield during cultivation in the presence of proline and tryptophan with respective values of 13.4±0.6 and 12.8±0.3 % (w/w, TFAs), which were 25 and 38% higher than when these fungi were grown with ammonium tartrate in AUMC11616.A and AUMC 6696.A. respectively, under shaking conditions at 150 rpm for 4 days at temperature of 28 ºC. The effects of environmental factors such as temperature, pH, fermentation time, and agitaion speed on the growth, total lipids, fatty acid composition, and GLA concentration of the target strains have been investigated and obtained a significant results in case of glutamine and asparagine as both individual nitrogen source. Our results demonstrated that nitrogen assimilation via amino acid metabolism, as well as the fluxes of glucose as carbon source, and its abiotic factors are integral to the increase oleaginicity of tested strains which isolated from unusual niches, that resulted in the enhanced lipid storage during nitrogen deprivation. Besides, rare studies have been carried out to investigate amino acids role in fermentation media, this study sheds light on R. pusillus and M. circinelloides as promising candidates for the potential applications of amino acids as N sources.